Association between perioperative prophylaxis with cefuroxime plus metronidazole or amoxicillin/clavulanic acid and surgical site infections in paediatric uncomplicated appendectomy: a Swiss retrospective cohort study - Isabella Bielicki; Hanna Schmid; Andrew Atkinson; Christian R. Kahlert; Christoph Berger; Nicolas Troillet; Jonas Marschall; Julia A. Bielicki; Swissnoso (Antimicrobial Resistance and Infection Control, 2023)
Abstract Objective We aimed to evaluate the association between post-appendectomy SSI rates and the two most commonly used regimens for perioperative antimicrobial prophylaxis in Swiss children. Methods We conducted a retrospective cohort study, analysing data from the Swiss national SSI surveillance database with a study period from 2014 to 2018. All hospitals undertaking paediatric appendectomies in Switzerland participate in the surveillance. We compared the cumulative incidence and odds of post-appendectomy SSI within 30 days of surgery in children ≤ 16 years of age undergoing appendectomy for uncomplicated appendicitis and receiving perioperative antimicrobial prophylaxis with cefuroxime plus metronidazole or with amoxicillin/clavulanic acid using multivariable adjusted logistic regression and propensity-score matching. Results A total of 6207 cases were recorded in the study time frame. Overall SSI cumulative incidence was 1.9% (n = 119). 4256 children (54.9% male, median (IQR) age 12 [10, 14] years) received either cefuroxime plus metronidazole (n = 2348, 53.8% male) or amoxicillin/clavulanic acid (n = 1491, 57.0% male). SSI cumulative incidence was 1.1% (25/2348) among children receiving cefuroxime plus metronidazole and 2.8% (42/1491, p < 0.001) when receiving amoxicillin/clavulanic acid. The administration of cefuroxime plus metronidazole was associated with statistically significantly lower SSI odds compared to amoxicillin/clavulanic acid (aOR 0.35, 95%CI [0.20, 0.61], p < 0.001), and this was confirmed upon propensity-score matching. Conclusion We found lower odds of post-appendectomy SSI in children receiving cefuroxime plus metronidazole compared to amoxicillin/clavulanic acid. Treating amoxicillin/clavulanic acid as the baseline, only 55 children need to receive cefuroxime plus metronidazole perioperative prophylaxis to avert one SSI. Existing guidelines recommending amoxicillin/clavulanic acid may need to be revised. Trial registration ISRCTN47727811, registered retrospectively.